TREATMENT OF PATIENTS WITH CHRONIC ISCHEMIC HEART DISEASE IN REAL CLINICAL PRACTICE ACCORDING TO THE DATA FROM PROGNOZ IBS REGISTER (PART 2) - S. N. Tolpygina; Yu. N. Polyanskaya; S. Yu. Martsevich (Столичная издательская компания, 2015)
Aim. To assess the quality of drug therapy and its correspondence with current clinical guidelines in patients with proven stable ischemic heart disease (IHD) before admission, during inpatient stay in hospital and after hospital discharge. Material and methods. Data on 550 patients (from PROGNOZ IBS register) with detected stenosis of at least one coronary artery ≥50% were included in the analysis. Assessment of the quality of drug therapy was conducted in patients who made a follow-up visit in 3.9 years after the reference hospitalization (n=303) using a specially designed questionnaire. Adherence to treatment was studied using a phone survey. Results. According to PROGNOZ IBS register data we revealed low prescription frequency of drugs with proven effects on the cardiovascular risk in patients with stable IHD prior to hospital admission and significant pharmacotherapy improvement in specialized cardiology hospital. In specialized hospital the rate of aspirin use increased by 30%, statins - by 80%, beta-blockers - by 70%, ACE inhibitors - by 60% (p<0.0001). These medications prescription frequency decreased by 15-20% on the average in 3.9 years after discharge. Conclusion. We found significant improvement in pharmacotherapy quality of patients with stable IHD during stay in cardiology hospital, and pharmacotherapy quality reduction after discharge.